![\frac{ {x }^{2} - 9 }{3x + 9} \frac{ {x }^{2} - 9 }{3x + 9}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bx+%7D%5E%7B2%7D+-+9+%7D%7B3x+%2B+9%7D++)
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo-a-passo:
Propriedade: a²-b²=(a-b)(a+b)
x²-9=x²-3²=(x-3)(x+3)
(x²-9)/(3x+9)=
(x²-9)/3(x+3)=
(x-3)(x+3)/3(x+3)=
(x-3)/3
Perguntas interessantes
Matemática,
8 meses atrás
Biologia,
8 meses atrás
Ed. Física,
8 meses atrás
Inglês,
10 meses atrás
Matemática,
10 meses atrás
Informática,
1 ano atrás